2020
DOI: 10.1101/2020.03.29.013649
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NAD+prevents septic shock-induced death by non-canonical inflammasome blockade and IL-10 cytokine production in macrophages

Abstract: Non-canonical inflammasome activation is crucial in the development of septic shock promoting pyroptosis and pro-inflammatory cytokine production via caspase-11 and Gasdermin-D (GSDMD). Here, we show that NAD + treatment protected mice towards bacterial and LPS induced endotoxic shock by blocking the non-canonical inflammasome specifically. NAD + administration impeded systemic IL-1β and IL-18 production and GSDMD-mediated pyroptosis of macrophages via the IFN-β/STAT-1 signaling machinery. More importantly, NA… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Consistent with our results, previous works have shown that boosting NAD+ levels by administering NAD+ or other NAD+ biosynthetic precursors (i.e., Niacin, NAM, and NR) alleviates the polymicrobial sepsis in different animal models. Indeed, it has been shown that the treatment with a high dose of NAD+ prior to a lethal dose of E. coli or LPS resulted in a marked increase in survival in mice ( Iske et al, 2020 ). Furthermore, administration of high-dose of Niacin to rats subjected to LPS-induced endotoxemia attenuated lung inflammation, reduced histologic lung damages, and improved survival at 72 h post injection ( Kwon et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, previous works have shown that boosting NAD+ levels by administering NAD+ or other NAD+ biosynthetic precursors (i.e., Niacin, NAM, and NR) alleviates the polymicrobial sepsis in different animal models. Indeed, it has been shown that the treatment with a high dose of NAD+ prior to a lethal dose of E. coli or LPS resulted in a marked increase in survival in mice ( Iske et al, 2020 ). Furthermore, administration of high-dose of Niacin to rats subjected to LPS-induced endotoxemia attenuated lung inflammation, reduced histologic lung damages, and improved survival at 72 h post injection ( Kwon et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular NAMPT converts nicotinamide to nicotinamide mononucleotide and is responsible for most of the NAD+ formation in mammals. Administration of NAD + prevents murine septic shock [34]. Extracellular NAMPT activates TLR4, promotes B cell maturation, and inhibits neutrophil apoptosis [35].…”
Section: Discussionmentioning
confidence: 99%